2012
DOI: 10.1017/s0007114512004837
|View full text |Cite
|
Sign up to set email alerts
|

Serum response to supplemental macular carotenoids in subjects with and without age-related macular degeneration

Abstract: Macular pigment (MP) is composed of lutein (L), zeaxanthin (Z) and meso-zeaxanthin (MZ). The present study reports on serum response to three different MP supplements in normal subjects (n 27) and in subjects with age-related macular degeneration (AMD) (n 27). Subjects were randomly assigned to: Group 1 (20 mg L and 2 mg Z), Group 2 (10 mg L, 2 mg Z and 10 mg MZ) or Group 3 (3 mg L, 2 mg Z and 17 mg MZ). Serum carotenoids were quantified at baseline, and at 4 and 8 weeks using HPLC. Response data for normal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…Recent data from our laboratory show that optimal enrichment of MP is dependent upon inclusion of MZ (along with L and Z) in the supplement formulation 79 , 10 MZ is believed to be particularly important for the following reasons. First, MZ is the dominant macular carotenoid at the foveal epicenter,8 and is therefore ideally located to exert optimal antioxidant activity and short-wavelength light filtration at the central macula, the specialized part of the retina responsible for color vision and high spatial resolution 11.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from our laboratory show that optimal enrichment of MP is dependent upon inclusion of MZ (along with L and Z) in the supplement formulation 79 , 10 MZ is believed to be particularly important for the following reasons. First, MZ is the dominant macular carotenoid at the foveal epicenter,8 and is therefore ideally located to exert optimal antioxidant activity and short-wavelength light filtration at the central macula, the specialized part of the retina responsible for color vision and high spatial resolution 11.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 provides a summary of MZ supplementation studies in combination with L/RZ. Human clinical studies demonstrate MZ's protective role for eye health and defense against AMD [26][27][28][29][30][31]. Overall, in these studies, MZ was observed in blood after supplementation.…”
Section: Bioavailabilitymentioning
confidence: 85%
“…Importantly, for this experiment we purified our L standard via HPLC, as previous work by our laboratory indicated the presence of all Z isomers (including MZ) in DSMprovided L standards. 38 Of note, it has also been suggested that MZ may be generated from L as a result of an enzymatic process at the macula, but such a hypothesis has yet to be investigated. 28 Also, and of interest, a recent investigation of serum carotenoid response following supplementation with different macular carotenoid formulations identified an unexpected peak with the spectrophotometric characteristics of MZ in the serum of subjects supplemented with 20 mg of L and 2 mg of Z (Ultra Lutein from Natural Organics Inc., Melville, NY, USA: L provided by FloraGLO, which is a registered trademark of Kemin Health, L.C., Kemin Industries, Inc. Des Moines, IA, USA).…”
Section: Origin Of the Macular Carotenoidsmentioning
confidence: 99%
“…Given that this was an unexpected finding, we reanalysed random serum samples from these subjects in order to confirm or refute our observation, and confirmed that MZ was, indeed, present. 38 We then tested the intervention formulation, and determined that it did, in fact, contain MZ (0.3 mg/capsule) (Figure 2), although MZ was not claimed on the product label.…”
Section: Origin Of the Macular Carotenoidsmentioning
confidence: 99%